ANALISIS STRUKTUR BIAYA, PENGELUARAN MODAL, DAN PROFITABILITAS PERUSAHAAN SEBELUM DAN SESUDAH PERUBAHAN KEEMPAT UU PPH 1984 (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Jessica Natanael Gunawan; Widi Hidayat; Sudibjo Sudibjo (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2020)
Introduction: Tax rate changes in Income Tax Law 1984 can be provided companies more beneficial so investment and tax revenue should be increased. The change in tax regulation will be affect to companies’ cost structure. Tax influence capital budgeting by tax effect in cash flow calculation and companies’ longterm capital expenditure too. In the end, cost structure and capital expenditure activities change will be affect companies’ net income after tax.Methods: Almost all companies which listed in stock exchange are manufacture industry, so manufacture handle an important part in Indonesian economic. To see the effect of tax regulation changes which is recently valid, then need to do comparison between before and after period of implementation Income Tax Law changes. The sample is taken by using purposive sampling from manufacture companies which listed in Indonesia Stock Exchange. The data is secondary data, financial annual report since 2008 up to 2010.Results: The result for hypothesis testing show that cost structure of manufacture industry is statistically different. Conclusion and suggestion: Capital expenditure and profitability of manufacture industry is not statistically different before and after period of implementation Income Tax Law 1984.